A Study on Contagious Bovine Pleuropneumonia in Khartoum State, Sudan - Isam Karam; Zaki A.Z.S.A; Elshalalli A.A (Journal of Veterinary Healthcare, 2017)
The study was carried out to investigate the occurrence of contagious bovine pleuropneumonia CBPP in Khartoum state. One-hundred twenty-two pneumonic lung tissue samples were collected from different slaughterhouses (116 samples most of which from local breed cattle) and from the field (six samples from cross breed cattle). Two-hundred and fifty-seven serum samples were collected randomly from cattle in different areas of the state. Tissue samples were cultivated using the standard mycoplasma procedures. Mmm was isolated from three pneumonic lungs collected from the field while no isolates were recovered from slaughterhouse samples. Histopathological sections from the positive samples revealed the typical picture of the CBPP which include fibrinonecrotic pneumonia within filtration of inflammatory cells and fibrin and distention of interlobular septae. One hundred and eight out of 257 serum samples were found positive for antibodies against Mmmusing complement fixation test (CFT). Findings of this study confirmed the presence of CBPP in Khartoum state by the isolation and identification of the causative agent.
Keywords: mycoplasma